Upper Maastrichtian and Danian bryozoans from Northern Patagonia, Argentina - Brezina, Soledad Silvana (2021)
The specimen-rich and diverse bryozoan fauna encrusting oyster shells from the Maastrichtian and Danian Jagüel and Roca formations in the Neuquén Basin (Patagonia, Argentina) is described. Thirteen cyclostome species are recorded, along with 18 cheilostomes. We introduce two new species: Akatopora kaufmanni sp. nov. and Eoporella lunata gen. et sp. nov. The latter is a homeomorph of the common Miocene–Recent genus Microporella. Ten of the cyclostomes and ten of the cheilostomes could not be identified at species-level because of preservational limitations or lack of diagnostic characters in the available specimens. The most common bryozoans present are sheet-like colonies, among which the ascophoran cheilostome Balantiostoma is particularly well represented. Results show that in northern Patagonia the diversity of encrusting bryozoans associated with oyster shells exhibits no major changes across the K/Pg boundary. However, an important increase in the diversity is recorded during the upper Danian.